2012
DOI: 10.7557/2.32.2.2274
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual model for migratory tundra caribou to explain and predict why shifts in spatial fidelity of breeding cows to their calving grounds are infrequent

Abstract: Calving grounds of migratory tundra caribou (Rangifer tarandus) have two prominent characteristics. Firstly, the cows are gregarious, and secondly, the annual calving grounds spatially overlap in consecutive years (spatial fidelity). The location of consecutive annual calving grounds can gradually shift (either rotationally or un-directional) or more rarely, abruptly (non-overlapping). We propose a mechanism to interpret and predict changes in spatial fidelity. We propose that fidelity is linked to gregariousn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…One explanation is that there was a true numerical decline in Beverly herd size as death rates consistently exceeded birth and recruitment rates. The shift in calving distribution to the Ahiak herd's calving ground between 2006 and 2009 was a consequence of the collapse in calving densities as the remaining Beverly cows switched to maintain the advantages of gregarious calving (Gunn et al, 2012). If this explanation is correct, then the Beverly herd is no longer identifiable as a distinct herd.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…One explanation is that there was a true numerical decline in Beverly herd size as death rates consistently exceeded birth and recruitment rates. The shift in calving distribution to the Ahiak herd's calving ground between 2006 and 2009 was a consequence of the collapse in calving densities as the remaining Beverly cows switched to maintain the advantages of gregarious calving (Gunn et al, 2012). If this explanation is correct, then the Beverly herd is no longer identifiable as a distinct herd.…”
Section: Introductionmentioning
confidence: 93%
“…The Beverly herd has three immediate neighbouring herds with traditional calving grounds recorded through Aboriginal knowledge and aerial surveys: the Qamanirjuaq traditional calving grounds about 400 km to the southeast (Heard, 1983;BQCMB, 1999a, b), the Bathurst calving grounds about 450 km to the northwest (Heard, 1983;Gunn et al, 2012), and the Ahiak calving grounds 250 km north along the Queen Maud Gulf coast (Heard et al, 1987;Gunn et al, 2000Gunn et al, , 2013a (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of barren-ground caribou is density-dependent such that range expansion and contraction are a function of the size of the herd (Simmons et al 1979, Bergerud et al 1984, Heard and Calef 1986, Messier et al 1988, Couturier et al 1990, Gunn et al 2012. Gunn et al (2013) reported that the winter range of the Bathurst herd has contracted since 2002, corresponding to the decline of the herd.…”
Section: Introductionmentioning
confidence: 99%
“…Heard and Calef (1986) and Heard and Williams (1992) suggested that tundra wolf populations respond numerically to changing caribou densities. Space-use patterns of barrenground caribou are density-dependent where the expansion and contraction of their range is a function o f the population size of the herd (Simmons et al 1979, Bergerud et al 1984, Heard and Calef 1986, Messier et al 1988, Couterier et al 1990, Gunn et al 2012. When caribou are abundant, the herd returns earlier to the southern portions of the summer range and within closer proximity to the denning areas of wolves, thus providing wolves with greater access to prey when the nutritional demands of pups are high.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation